CD34+ hematopoietic progenitor cells enumeration and mononuclear cell count: an experience from a tertiary care centre - Bhat, Shuaeb; Hussain, Saleem; Noor, Huma; Shoket, Nadeem (International Journal of Research in Medical Sciences, 2019)
Background: This study was conducted to assess the CD34+ hematopoietic progenitor cells enumeration by flow cytometry and the utility of performing mononuclear cell count before performing the Stem cell enumeration. Collection was done on two consecutive days with CD34+ hematopoietic progenitor cell enumeration of both the samples. Mononuclear cell counts were done in all the patients. The purpose of the study was to do counts directly from the leukapheresis pack and see the reliability of this practice. Methods: Samples were collected from the leukapheresis pack and subjected to mononuclear cell count and CD34+ hematopoietic progenitor cells enumeration by flow cytometty before harvesting. Results: A total of 66 samples from 34 patients were taken up for the study. 76.47% of our cases were that of multiple myeloma and 17.64% of the cases were that of non Hodgkin lymphoma and 2.94% cases each of neuroblastoma and Hodgkin lymphoma. It was noted that the mononuclear cell counts correlated well with the CD34+ HPC in most of the cases with MNC being above 4 x 108 per pack per kg body weight in cases where CD34+ HPC counts were more than the desired lower limit of 2 x 106 per pack per kg body weight. Conclusions: It was observed that flow cytometric enumeration of CD34+ hematopoietic progenitor cells directly from the leukapheresis pack gave satisfactory results even without doing peripheral blood CD34+ HPCs enumeration before leukapheresis. Also, in our study we were able to set a limit of mononuclear Cell at 4 x 108 per pack/kg BW as counts beyond that always correlated with the more accurate flow cytometric method of CD34+ HPC count of more than 2 x106 per pack/kg body weight, therefore acting as a crude method for assessing the mobilization.